2013
DOI: 10.1093/cid/cit790
|View full text |Cite
|
Sign up to set email alerts
|

Protection by BCG Vaccine Against Tuberculosis: A Systematic Review of Randomized Controlled Trials

Abstract: Absence of prior M. tuberculosis infection or sensitization with environmental mycobacteria is associated with higher efficacy of BCG against pulmonary tuberculosis and possibly against miliary and meningeal tuberculosis. Evaluations of new tuberculosis vaccines should account for the possibility that prior infection may mask or block their effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
660
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 770 publications
(716 citation statements)
references
References 27 publications
8
660
0
15
Order By: Relevance
“…This potential appears largest if the vaccine is targeted at adolescents/adults, providing further evidence, along with the report on increased efficacy against pulmonary TB in screened adults (31), for a recently suggested strategy (32) of giving bacillus Calmette-Guérin to screened adults. However, for those individuals already infected with TB or other environmental Mycobacteria (i.e., who fail the screen), there is still a need, and a large market, for a new TB vaccine.…”
Section: Discussionmentioning
confidence: 78%
“…This potential appears largest if the vaccine is targeted at adolescents/adults, providing further evidence, along with the report on increased efficacy against pulmonary TB in screened adults (31), for a recently suggested strategy (32) of giving bacillus Calmette-Guérin to screened adults. However, for those individuals already infected with TB or other environmental Mycobacteria (i.e., who fail the screen), there is still a need, and a large market, for a new TB vaccine.…”
Section: Discussionmentioning
confidence: 78%
“…[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] A recent meta-analysis of the efficacy of BCG vaccine against the pulmonary, meningeal and disseminated forms of TB included 21 randomized or quasi-randomized clinical trials: 18 involving patients with pulmonary TB, and 6 involving patients with meningeal and/or military forms. 30 The panel marginally supports a recommendation for use subjects vaccinated at birth (RR 0.41, 95% CI 0,29-0.58). There were some differences related to latitude; average protection was lower in the studies conducted in places at latitudes of 0-20 and 20-40 than in those conducted at higher latitudes.…”
Section: What Is the Current Role Of Bcg Vaccination?mentioning
confidence: 99%
“…This led to the emergence of genetic and antigenic differences among the marketed strains, 3 which gave rise to concerns about the safety and efficacy of the different vaccines. 4,5 BCG vaccine is widely used in countries in which TB is highly endemic, and where all newborns receive a single intradermal dose immediately after birth or later in infancy. [6][7][8] It is estimated that it has so far been administered more than 4 billion times, and that 120 million children are vaccinated every year.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The variation of protection by BCG may be attributed to different types of BCG, to genetic differences between populations, and to coldchain maintenance of BCG. 18 In addition, another important issue affecting this variability is the exposure to environmental mycobacteria.…”
mentioning
confidence: 99%
“…18 In addition, another important issue affecting this variability is the exposure to environmental mycobacteria. 20 A systematic review of 21 randomized controlled trials evaluating the protection by BCG revealed that BCG imparted greater protection in northern latitudes, which may be due to less exposure to non-tuberculous mycobacteria (NTM) faced by vaccine recipients in these areas. 20 In another study from China, the researchers also found that the immune response to BCG vaccination varied according to the NTM exposure among neonates.…”
mentioning
confidence: 99%